The relationship between mental health knowledge and help-seeking behavior among psychology students at Nusa Cendana University - Nggalamanu, Graicella Mutiara Were; Benu, Juliana Marlin Y.; Ratu, Feronika; Anakaka, Dian Lestari (Universitas Nusa Cendana, 2024)
This study highlights mental health as a global health challenge that requires serious attention, especially among students. The main objective is to examine the relationship between Mental Health Knowledge and Help-Seeking Behavior among psychology students at Nusa Cendana University. Using a quantitative approach, this research employs proportional sampling and two measurement scales: the Adolescents' Mental Health Knowledge Questionnaire to assess mental health knowledge, and the General Help-Seeking Questionnaire to evaluate help-seeking behavior. The data analysis method used is Pearson's product-moment correlation, with the aid of Microsoft Excel and IBM SPSS Statistic 26 software. The results indicate a significant relationship between mental health knowledge and help-seeking behavior, as evidenced by a significance value of 0.000 (below 0.05). The correlation between the two variables is 0.435, which indicates a moderate and positive correlation. This means that the lower the mental health knowledge, the lower the help-seeking behavior. The study emphasizes the importance of students' proactive role in increasing their awareness of mental health. Students are encouraged to seek information from credible sources, such as books, scientific articles, seminars, and training sessions. Additionally, they are advised to engage in discussions with lecturers or supervisors, as well as participate in mental health-related organizations to broaden their knowledge. Sharing knowledge through discussions with peers is also expected to help strengthen their understanding of mental health.